Influencia del ejercicio físico en la capacidad funcional de ancianos institucionalizados - Scarabottolo, Catarina Covolo [UNESP]; Garcia Júnior, Jair Rodrigues; Gobbo, Luis Alberto [UNESP]; Alves, Marcelo José; Ferreira, Aline Duarte [UNESP]; Zanuto, Everton Alex Carvalho [UNESP]; de Oliveira, Weber Gutemberg Alves; Christofaro, Diego Giulliano Destro [UNESP] (FapUNIFESP (SciELO), 2017)
Introduction: With the rapid increase in life expectancy, systematic physical exercise programs can have a good influence on the functional capacity of the elderly, especially in relation to institutionalization. Objective: To analyze the association between a systematic physical exercise program and functional capacity in institu-tionalized elderly. Methods: The sample included 30 elderly subjects (16 women and 14 men) aged 60 years or older (mean age = 74.43), divided into a control group (n=16) and a training group (n=14), residents in a long-stay institution. A training protocol of 12 weeks, two weekly sessions, was applied, and functional capa-city was assessed before and after the intervention, through chair lift tests (lower limb strength), upper limb strength, timed up and go and handgrip dynamometry. The analysis pre and post-training of intervention and control groups was performed using paired Student t test and the ANOVA test for repeated measures. The level of significance was set at 5%. Results: The main statistical significance were found for the following functional tests: upper limb strength (training 15.6±4.1 x control 10.7±6.6 rep, p<0.05) and chair lift test (training 11.0±4.0 x control 8.0±3.1 rep, p<0.05). Conclusion: The protocol used proved to be effective in improving some of the functional capabilities of the institutionalized elderly.
Influência do exercício físico na capacidade funcional de idosos institucionalizados
Influence of physical exercise on the functional capacity in institutionalized elderly
Keywords: Aged; Health; Homes for the aged; Life expectancy; Longevity